ACETYLSALICYLIC ACID AND PREVENTION OF FATAL OUTCOMES IN CARDIOVASCULAR DISEASE: SELECTING MEDICATION FORM AND DOSE - O. V. Averkov (Российский кардиологический журнал, 2012)
This analytic paper presents the evidence on the potential of acetylsalicylic acid (ASA) for the mortality reduction in patients with cardiovascular disease. The focus is on the “minimal” effective dose of ASA, in terms of its effects on survival. The discussion of the ASA form and dose selection also mentions the impact of ASA tolerability on its effectiveness. The need for the balance between antiischemic effectiveness and safety (haemorrhage safety, in particular) justifies the use of varied ASA doses. The benefits of so-called enteric coated ASA forms are also summarised.